Internal rhythm and direction of significance in the examples of Uqila al-Kalbi poetry - خضر, يعرب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Poetry is a musical organization of speech. If the ear hears it, it feels the joy that it feels when it hears music. It is an essential part of poetry, and one of the best elements of suggestion in it. The internal music of poetry emanates from the unity of the motive in the sentence according to the feeling it expresses, and the matching of the feeling with the expressive music. It is the matter that constitutes the unity of the entire poem, and this internal music should not be monotonous in any way because it is expressive and suggestive, giving the words the maximum meaning that can be expressed. Thus, the sound values of the expressive sentences vary in one poem, and the time intervals between them vary, and create a kind of Movement and vitality within the poetic text, known as poetic rhythm. This research aims to study the internal rhythm of Uqila al-Kalbi’s poetry in an audio-semantic study, and to show the phenomena that contributed to the production of the internal music of the text, and to search for the relationship of the internal poetic music to directing the connotations that the speaker intends to direct to the recipient. Its importance is that it is a study of internal musical phenomena in poetry Al-Kalbi's obstruction, in order to reveal its variations and its effect in directing meaning.